Assessment and Knowledge of Long-Term Steroid Use and Its Related Cataract & Glaucoma Development Among Hail Residents - Algorinees RM; Alshammari BJ; Albalawi MA; Almozaini KH; Alharbi TF; Alshammari TA; Alghaslan MA; Almansour RN (Clinical Ophthalmology)
Rakan Mosa Algorinees, Bader Jazzaa Alshammari, Mansour Ahmed Albalawi, Khaled Homoud Almozaini, Talal Fahad Alharbi, Turki Ali Alshammari, Manar Ali Alghaslan, Rana Nasser Almansour Department of Ophthalmology, College of Medicine, University of Hail, Hail, Saudi ArabiaCorrespondence: Rakan Mosa Algorinees, Department of Ophthalmology, College of Medicine, University of Hail, Hail, Saudi Arabia, P.O.Box. 2240, Tel +966165320699, Email Algorinees@hotmail.comPurpose: This study evaluated the prevalence of steroid use and public awareness of its ocular complications, including cataracts and glaucoma, in Hail, Saudi Arabia.Methods: A descriptive cross-sectional study was conducted in Saudi Arabia’s Hail region from September 2024 to November 2024, targeting eligible and accessible residents aged 18 years or older. Data was collected using a pre-structured online questionnaire developed by the researchers. The final version was independently reviewed and distributed online to eligible applicants. The collected data included socio-demographic information, medical history, personal habits, and knowledge of potential associations between steroid use and eye diseases. Data analysis was done using SPSS version 26 based on descriptive statistics and relations using the Pearson X2 test and exact probability test.Results: The study surveyed young adults aged 18 years or more, with 51.8% being male. Most participants (74.5%) had never used steroids. Eye drops were the most common, followed by topical creams. 30.8% of participants had good knowledge about long-term steroid use with cataract development, while 21% had a good knowledge level for steroid use and glaucoma development. In total, 24.7% had good knowledge about eye diseases.Conclusion: A study in Hail, Saudi Arabia reveals a significant lack of public knowledge about the long-term use of steroids and associated ocular risks, particularly cataracts and glaucoma. Despite never using steroids, those who have used them often prefer short-term treatments. The study recommends improved patient education, health interventions, and regulation of over-the-counter steroids usage, especially for younger populations and those without healthcare backgrounds.Keywords: long-term steroid use, cataract, glaucoma, knowledge, Saudi Arabia